HUKUM ADMINISTRASI NEGARA DALAM PENANGGULANGAN BENCANA: PEMBELAJARAN DARI PANDEMI COVID-19 - Ayu Miya Maryani; Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2025)
The COVID-19 pandemic has been a real test of the effectiveness of state administrative law in disaster management. This study examines how the legal and regulatory framework in Indonesia responds to emergency situations during the pandemic, and identifies key lessons for future improvement. The main findings show that policy flexibility, inter-agency collaboration, and transparency in decision-making are crucial factors for effective disaster management. In addition, the integration of technology and innovation within a legal framework is essential for rapid and data-driven response adaptation. The study recommends reforms in state administrative law to face future challenges in a more agile and coordinated manner.